Optimizing Blood Inventory Control Using EOQ and Forecasting Methods - Sa'Diyah, Fatimatus; Nurmasari, Nuraini Desty (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to analyze and optimize blood supply inventory control at the Blood Transfusion Unit (UTD) of PMI Malang City by addressing stockout and overstock problems that affect operational efficiency, cost management, and healthcare service quality. Design/Methodology/Approach – This study employs a quantitative approach using deterministic Economic Order Quantity (EOQ) analysis combined with safety stock and reorder point methods to determine optimal inventory policies for blood supplies. Historical inventory data from January 2022 to October 2024, consisting of 15 stockout events and 19 overstock events, were analyzed. Holt’s exponential smoothing method was applied to identify demand patterns and forecast future blood supply requirements for blood types A, B, O, and AB. Findings – The results provide optimal quantities of blood bags for each replenishment period, safety stock levels, and reorder points for each blood type. The implementation of the EOQ method significantly improves inventory efficiency by reducing total inventory costs by more than 50% annually for all blood types. These findings demonstrate that systematic inventory control can minimize shortages and excess stock while ensuring the availability of blood supplies for medical services. Originality/Value This research is original in integrating EOQ, safety stock, reorder point, and Holt’s exponential smoothing to optimize blood supply inventory control in a single operational model. The findings provide practical value by offering a cost-efficient and data-driven framework for managing blood inventories and reducing both shortages and excess stock.